Contributions to the knowledge of Dichelops Spinola: description of a new species of Dichelops (Diceraeus) and of the male of Dichelops (Prodichelops) divisus (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini) - Poock-Da-Silva, Priscila; Barão, Kim Ribeiro; Grazia, Jocelia (Zootaxa, 2013)
A new species of Dichelops (Diceraeus) Dallas and the so-far unknown male of Dichelops (Prodichelops) divisus (Walker, 1867) are described, based upon morphological characters. D. (Dice.) caatinguensis sp. nov. is compared to the other four species of Diceraeus. Revised keys to separate the subgenera of Dichelops and the species of Diceraeus are also presented. D. (P.) divisus male is described and compared to the type species. Comparative illustrations of external and internal genitalia of the species are provided.